Analysis of nonlinear thermal radiation and higher‐order chemical reactions on the non‐orthogonal stagnation point flow over a lubricated surface. Issue 2 (27th November 2019) - Abbasi, Aamar; Riaz, Iqra; Farooq, Waseh; Ahmad, Manzoor
Abstract: A numerical study is performed to discuss the heat and mass transfer on oblique stagnation point flow over a lubricated surface with nonlinear thermal radiation and higher‐order chemical reactions. The problem is formulated using basic conservation laws of mass, momentum, energy, and mass concentration in terms of partial differential equations along with nonlinear boundary conditions. These governing equations are transformed into ordinary differential equations by means of similarity transformations. The system of resulting ordinary differential equations are solved numerically by an implicit finite difference scheme known as the Keller–box method. The quantities elaborated in the problem, such as velocity, temperature, skin friction, and local Nusselt and Sherwood numbers are analyzed for several values of involved parameters. The obtained results are presented through various graphs and tabular data and showed a good agreement with the existing results in the literature, which are the subcases of the present work. The heat transfer rate enhances with nonlinear thermal radiation and mass transfer rate decreases with increasing the order of chemical reaction.